Hand gestures for continuous locomotion and snap turn for VR Experiences - Kronemberger, Victhor; Cherullo, Renato; Azevedo, Thiago; Porcino, Thiago; Raposo, Alberto (Anais do Simpósio de Realidade Virtual e Aumentada (SVR); 2023: Anais do XXV Simpósio de Realidade Virtual e Aumentada, 2023)
Virtual Reality (VR) allows users to move through a plethora of immersive 3D worlds without leaving their spot with techniques such as smooth continuous locomotion. Nowadays, the standard is to do those sorts of inputs with controllers, however, hand tracking is an ever-growing technology that is gradually becoming relevant as one of the main input modalities available. The purpose of this study is to investigate which gestures works better to allow the user to move continuously in Virtual Environments (VEs) while also allowing it to do quick rotations in 45 and 180 degrees (snap turns). The inputs are compared in terms of efficiency, usability, and user preference.